Putusan MK dan Evaluasi Ambang Batas Pencalonan Presiden: Arah Revisi UU Pemilu dan Dampaknya terhadap Demokrasi di Indonesia - Ghina Aven (Jurnal Hukum Lex Generalis, 2025)
This article examines the Constitutional Court (MK) ruling and the direction of the revision of Law Number 7 of 2017 concerning General Elections related to the presidential threshold. The analysis focuses on Constitutional Court Decisions Number 53/PUU-XV/2017 and Number 74/PUU-XXI/2023 using philosophical, juridical, and sociological approaches. The results of the study show that although the Constitutional Court affirms the threshold as an open legal policy, this policy limits the sovereignty of the people and narrows political participation. Therefore, it is important to revise this provision so that it is in line with the principles of substantive democracy that guarantee openness, political representation, and electoral justice.